FOREST LAW ENFORCEMENT GOVERNANCE AND TRADE – VOLUNTARY PARTNERSHIP AGREEMENT SEBAGAI INSTRUMEN UNI EROPA DALAM MENGONTROL PERDAGANGAN KAYU DI INDONESIA - Ana Muryanti (HI 16 UMY 055, 2016)
*55 This paper explains the EU's efforts to combat illegal logging in Indonesia through an international regime such as Forest Law Enforcement Governance and Trade - Voluntary Partnership Agreement. International regime that was initiated by the European Union is ratified by Indonesia in 2007. After the FLEGT-VPA began to be implemented in 2013 in Indonesia, began to appear the evidence that led to the EU's efforts to control the timber trade in Indonesia using instruments FLEGT-VPA. The emergence of an effort to control this raises doubts about the EU's concern for environmental issues. ABSTRAK Paper ini mengeksplanasikan mengenai upaya Uni Eropa untuk memberantas illegal logging di Indonesia melalui sebuah rezim internasional berupa Forest Law Enforcement Governance and Trade - Voluntary Partnership Agreement. Rezim internasional yang digagas oleh Uni Eropa ini diratifikasi Indonesia pada tahun 2007. Setelah FLEGT-VPA mulai diimplementasikan pada tahun 2013 di Indonesia, mulai muncul adanya bukti-bukti yang mengarah pada upaya Uni Eropa mengontrol perdagangan kayu di Indonesia menggunakan instrumen FLEGT-VPA. Munculnya upaya pengontrolan ini menimbulkan keraguan mengenai kepedulian Uni Eropa terhadap isu lingkungan hidup.